Hi,
We know that:
a² -- b² = (a -- b)(a + b).
With a = x, and b = 4, we have:
x² -- 16 = x² -- 4² = (x -- 4)(x + 4).
As simple as that. Have you understood ?
Green eyes.
Use distributive property a(b + c) = ab + ac.
![2x(y^2+3)-5(3+y^2)=(2x)(y^2)+(2x)(3)+(-5)(3)+(-5)(y^2)\\\\=2xy^2+6x-15-5y^2](https://tex.z-dn.net/?f=2x%28y%5E2%2B3%29-5%283%2By%5E2%29%3D%282x%29%28y%5E2%29%2B%282x%29%283%29%2B%28-5%29%283%29%2B%28-5%29%28y%5E2%29%5C%5C%5C%5C%3D2xy%5E2%2B6x-15-5y%5E2)
Answer:
2.5 miles
Step-by-step explanation:
Answer:
the 2 one
Step-by-step explanation: